Mechanism System to Reduce the Pendulum Effect of a Load for Delivery Drone - bin Abd Wahid, Amirul Hilman; Ramli, Muhammd Faiz (Progress in Aerospace and Aviation Technology, 2023)
Unmanned aerial vehicles (UAVs), also referred to as "drones," are becoming more widely accepted as a typical form of transportation for a range of purposes in the logistics sector. Drones are anticipated to outperform traditional vehicles in a number of ways, including with a constant, quick speed, travel is straightforward, there is no exposure to traffic, and there is no requirement for physical transportation infrastructure. When an aircraft is in a sideslip, these surfaces generate sideward lift forces, which is known as the pendulum effect. The keel effect, also known as the "Pendulum Effect," occurs when the effect of sideways forces above the center of gravity in producing a rolling moment is increased by having a lower center of gravity. The load shift, also known as the pendulum effect, reduces flight efficiency and may unbalance the UAV, resulting in catastrophic failure. The purpose of this project is to construct a mechanism system to reduce the pendulum effect of a load for the delivery drone and to investigate the numbers of pendulum sway with the different types of loads. The mechanism for this project was constructed by using a 3D printer. The experiment process was used to carry out this project. This project's variables included various types of loads, string length, and the number of sways. The data obtained in this project are important to determine which design is the best for the delivery drone. Unfortunately, the data from the experiment gave the same result for all designs. For future studies try to come up with new concepts for how to construct the mechanism system to reduce the pendulum effect of a load for delivery drone and compare all the concepts.